Evaluation of Computed Tomography Scans of Neck Masses and Their Histopathological Correlation (Mugda Medical College Journal, 2026)
A cross-sectional, comparative study was conducted in the Department of Radiology & Imaging, Shaheed Suhrawardy Medical College Hospital, Dhaka, Bangladesh, between July and December of 2019, to assess the diagnostic usefulness of multi-detector computed tomography scans in the evaluation of neck mass by comparing with histopathological reports. A total of 40 patients were enrolled in the study. All relevant data was collected from history sheet of the patients and investigation reports. Computed Tomography findings and histopathological diagnosis were recorded in a pre-designed structured data collection sheet. Then histopathology reports were compared with computed tomography (CT) scan findings. The most common age group was 40-70 years (45%), followed by 15-40 years (35%) and